Key success factors creating values in Marketing: a study on Instant-Food-Products (IFPs) marketing in Bangladesh - Mohammad Bakhtiar Rana; Md. Masrurul Mowla; Md. Tarikul Islam (Universitas Trisakti, 2011)
The concern as a marketer is to determine the key success factors that create value for products to the consumers in Bangladeshi market with regard to selected IFPs. Doing business based on value delivered gives companies the means to get an equitable return for their efforts. This study focusing on three IFTs such as Noodles, Biscuits & C'alces, and Chip, has attempted to determine the key success factors that create value for these products to the customers and retailers. Factors are then thoroughly scanned in terms of their merits and weights on the basis of findings from consumers' and retailers' survey. Finally the higher weighted factors have been considered as the key success factors that create va lue for the IFPs in Bangladeshi market. Study reveals an interesting finding that price is not the most important factor that consumers firstly prioritize in order to buy a brand of instant food product, rather taste and quality is the priority that consumers first consider. Moreover, in addition to taste and quality, packaging, price, advertising and availability of the product have been found to be the most important key success factors for instant food product marketing in Bangladesh. As the economy moves forward living styles with consumption pattern are becoming diverse. The criteria of choosing an instant food product, therefore, have been greatly different and factor dependent Marketers need to pay more attention on marketing strategy formation with regard to taste & quality, packaging and advertising as well as product innovation.Key words: key-success-factors, value creation, instant-food products, Introduction